Kontribusi Nilai-Nilai Kearifan Lokal dalam Budaya Tradisi Macanan dan Kawin Cai Untuk Menguatkan Identitas Nasional Indonesia (Studi Kasus di Desa Adiraja Kabupaten Cilacap dan Desa Babakan Kabupaten Kuningan) - Sukmayadi, Trisna; Suyitno, Suyitno (Fakultas Ilmu Budaya Universitas Diponegoro, 2022)
AbstractNational identity is the identity of a nation that differentiates between one nation and another. Therefore, it is necessary to re-understand national identity which includes what constitutes the true identity of the Indonesian nation. This study aims to find the values of local wisdom in people's culture to strengthen national identity, using the type of case study research. The results showed that the Macanan and Kawin Cai traditions contained elements of local wisdom values, namely religious values (gratitude), caring, and obedience. Where these values contribute to strengthening national identity.Key words: culture, local wisdom, national identity